The Riddles of Jesus in John: A Study in Tradition and Folklore - North, Wendy Sproston (Journal of Semitic studies, 2002)
The Riddles of Jesus in John: A Study in Tradition and Folklore TomThatcher (Society of Biblical Literature Monograph Series 53). Society of Biblical LiteratureAtlanta 2000x + 306$45.00 0‐88414‐018‐0 , 1Darlington